Prototype Of Android-Based Face Detection Attendance Application Using Hog Method At PT. Thamrin Brothers Seluma - Agustin, Decki; Yupianti, Yupianti; Alinse , Rizka Tri (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
PT. Thamrin Brothers Seluma is a company engaged in the automotive trade, especially two-wheeled vehicles, which is located in Seluma Regency, Bengkulu Province, Indonesia. The company needs an attendance system that can improve the weaknesses of the current attendance system. If the equipment damage and there is a power outage, as a result, attendance is made manually, while the attendance system is very necessary in monitoring employee attendance every day at the company. The method used is the Hinstogram of Oriented Gardens, which is a method that helps detect faces in designing Android-based face detection attendance application. It will make it easier for users to make attendance by way of face detection using an Android smartphone. Besides that, PT. Thamrin Brothers Seluma can more easily monitor the attendance of its employees. Based on system testing at PT. Thamrin Brothers Seluma can be concluded that the design of the Android-based face detection attendance application has met what was expected by PT. Thamrin Brothers Seluma well.